Building occupant satisfaction towards indoor environmental quality of library - Tuan Nurul Asmaq, Tuan Kamaruddin; Norhidayah, Abdull (Penerbit Universiti Malaysia Pahang, 2023)
Indoor environment is an important factor to be considered while designing a building. The quality of the indoor environment for buildings that are not in the “non -profit” category is rarely given attention. The quality of a library’s indoor environment is crucial to be highlighted as modern people are spending 90% of their time in enclosed spaces. Disruption of the indoor environment can reduce the efficiency and satisfaction of the occupants. Occupants are going to feel insecure making their job in an unhealthful environment. The purpose of this study is to assess the building occupant satisfaction in library regarding indoor environment. A total of 85 questionnaires were distributed to the users of the Kemaman District Library in Terengganu. To investigate occupants’ satisfaction, quantitative approaches were applied and evaluated by using the Statistical Package for the Social Sciences. The results of a self-assessed occupant satisfaction survey revealed that the indoor environment quality, as well as the interior design, had a positive correlation and significant effect on occupant satisfaction. Interior design accounted for 39% of occupant satisfaction since the p-value is lower than significant value (β=0.390, p-value=0.000<0.05), whereas the indoor environment quality accounted with the largest beta coefficient (β=0.497, p-value=0.000<0.05) which has explained 49.7% of the variation in occupant satisfaction. When compared to the indoor environment quality, respondents were found to be less satisfied with the interior design. This study contributes to the proposal of interior design solutions to improve and maintain occupant satisfaction in the library.